Lawyer nation : the past, present, and future of the American legal profession - Brescia, Ray (New York University Press, 2024)
"At this time of tumultuous change and threats to the rule of law in the United States, Lawyer Nation explores the critical role that American lawyers have played since the nation's founding, and the role they must play today and in the future, in defending and advancing justice and inclusion in our multi-racial democracy"-- Provided by publisher.
Keywords: Practice of law -- United States.; Lawyers -- United States.; Droit -- Pratique -- États-Unis.; Avocats -- États-Unis.; LAW / Legal Profession.; Lawyers; Practice of law; United States